Terminal singularities, Milnor numbers, and matter in F-theory - Arras, Philipp Adam; Grassi, Antonella; Weigand, Timo (Journal of geometry and physics, 2017)
We initiate a systematic investigation of F-theory on elliptic fibrations with singularities which cannot be resolved without breaking the Calabi-Yau condition, corresponding to Q-factorial terminal singularities. It is the purpose of this paper to elucidate the physical origin of such non-crepant singularities in codimension two and to systematically analyze F-theory compactifications containing such singularities. The singularities reflect the presence of localized matter states from wrapped M2-branes which are not charged under any massless gauge potential. We identify a class of Q-factorial terminal singularities on elliptically fibered Calabi-Yau threefolds for which we can compute the number of uncharged localized hypermultiplets in terms of their associated Milnor numbers. These count the local complex deformations of the singularities. The resulting six-dimensional spectra are shown to be anomaly-free. We exemplify this in a variety of cases, including models with non-perturbative gauge groups with both charged and uncharged localized matter. The underlying mathematics will be discussed further in a forthcoming publication.
Gesehen am 18.12.2017